Chlorine dioxide gas slow-release film for strawberry preservation. (1st March 2023) - Ren, Liu; Jian, Wang; chongxing, Huang; Hongxia, Su; Haohe, Huang; Wanru, Luo; Jiejie, An; Hui, Zhao; Yangfan, Xu; Shuangfei, Wang
Abstract: The polymeric wall material of microcapsules has the function of encapsulation, protection, and controlled release of the active core material. In this study, sodium alginate (SA)-NaClO2 solution was encapsulated in ethylcellulose (EC) microcapsules using an emulsion-solvent evaporation method. The EC/SA-NaClO2 microcapsules were doped into polyvinyl alcohol (PVA) solution containing HCl, and an antimicrobial film was prepared using the solution casting method. Water vapor drives HCl into the interior of the microcapsules and reacts with NaClO2 in the microcapsules to release ClO2 gas to achieve antimicrobial properties. ClO2 gas can effectively inhibit the growth and reproduction of bacteria and molds on strawberry surfaces. The antimicrobial film inhibited the growth of E. coli by 99.9% and reduced the area of B. cinerea to <10%. Storage bags prepared from antimicrobial films could extend the shelf life of strawberries and maintain their sensory characteristics such as color, hardness, and moisture. Graphical abstract: Image 1 Highlights: The antibacterial film can release ClO2 gas at low humidity. The antibacterial film was continuously released at 25 °C and 55% RH for about 200 h. The film has excellent antibacterial properties against E. coli and B. cinerea. The antibacterial film was used for packaging and storage of fruits and vegetables. The antimicrobial film can extend strawberry shelf-life.